MISI HOLISTIK:: KU UTUS ENGKAU KE DUNIA UNTUK MEMBERITAKAN KERAJAAN ALLAH BERDASARKAN URAIAN TEKS LUKAS 9:1-6 - Adi Putra; Tony Salurante (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2020)
Abstract: This research was conducted to provide a new understanding to the church about holistic mission, especially based on the description in the text of Luke 9: 1-6. By using qualitative methods, the researcher then found several principles about the holistic mission as the conclusion of this study. First, a holistic mission is a mission that is carried out through a mission and is a continuation of God's mission to Jesus. Second, a holistic mission is a mission carried out by the apostles and furthermore by the Church as a mandate from Jesus to provide significant social change or impact in the midst of society. Third, a holistic mission is a mission that focuses on a clear mission object and requires transformation or change. Fourth, a holistic mission is a mission that preaches the Kingdom of God. Fifth,